THE RESISTANCE OF THE PEGAYAMAN ISLAMIC COMMUNITY AGAINST STIGMA AND IDENTITY RETENTION STRATEGIES IN BULELENG REGENCY - A.A. Ngurah Anom Kumbara; A A Sagung Kartika Dewi (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2022)
The issue of disharmony and conflict based on differences in culture, religion, history, and ethnicity still often arises in Indonesia, including in Bali. One of the related phenomena is the stigmatization of the Islamic community in Pegayaman Village which causes various forms of violence, both physical and symbolic. The aims of this study are 1) to understand the reasons underlying the emergence of stigmatization; 2) describe the forms of stigma, and 3) examine strategies for resistance to stigma and maintaining the identity of the Pegayaman Islamic Community in Buleleng Regency. Data was collected using in-depth interviews, observation, document studies, and focus group discussions. Data analysis used a critical interpretation approach with the stages of reduction, presentation, drawing conclusions and verification. This study finds that the reasons underlying the stigmatization of the Pegayaman Islamic Community include, (a) historical experience factors, (b) religious ideology, and ethnicity, (c) construction of reality for various interests, and (d), self-reflexivity, 'we'. and 'them'. Forms of stigma include, (a) labeling, (b) stereotypes, (c) separation; and (d) discrimination. The resistance and identity defense strategies that have been carried out include (a) direct and open strategies through demonstrations, dialogue with the bureaucracy, politicians, media, and regulation of interfaith marriage restrictions, as well as (b) strategies to improve the quality of life of community members through hard work, status improvement economics, children's education, instilling Islamic values ??from an early age, and building cooperation in social, religious, and economic activities. This strategy is effective in minimizing the stigma of society towards the Pegayaman Islamic Community. Keywords : Identity, Islamic community of Pegayaman, resistance, strategy, stigma